2022
DOI: 10.3389/fnins.2022.1096734
|View full text |Cite
|
Sign up to set email alerts
|

Tuina for peripherally-induced neuropathic pain: A review of analgesic mechanism

Abstract: Peripherally-induced neuropathic pain (pNP) is a kind of NP that is common, frequent, and difficult to treat. Tuina, also known as massage and manual therapy, has been used to treat pain in China for thousands of years. It has been clinically proven to be effective in the treatment of pNP caused by cervical spondylosis, lumbar disc herniation, etc. However, its analgesic mechanism is still not clear and has been the focus of research. In this review, we summarize the existing research progress, so as to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Studies have shown that the pathological characteristics of lower back pain in patients with postpartum DRA are mainly caused by abdominal muscle spasm and myofascial incarceration[ 16 ]. Tuina can promote analgesic effects by stimulating different levels of targets[ 17 ]. Smith et al [ 18 ] reported that manual massage can alleviate the pain of childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the pathological characteristics of lower back pain in patients with postpartum DRA are mainly caused by abdominal muscle spasm and myofascial incarceration[ 16 ]. Tuina can promote analgesic effects by stimulating different levels of targets[ 17 ]. Smith et al [ 18 ] reported that manual massage can alleviate the pain of childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Acupressure stimulates the same acupoints as acupuncture with the use of fingers, hands, or elbows, based on traditional Chinese medicine (TCM) meridian theory. The analgesic mechanism of acupressure may primarily involve the suppression of peripheral inflammation through the regulation of inflammatory signal transduction and pain signal transduction pathway modulation of ion channels and inhibition of glial cell activation . Recently, clinical trials have attempted to examine the feasibility and effectiveness of SAA for the treatment of knee OA in postmenopausal women and older patients .…”
Section: Introductionmentioning
confidence: 99%
“…The analgesic mechanism of acupressure may primarily involve the suppression of peripheral inflammation through the regulation of inflammatory signal transduction 12 and pain signal transduction pathway 13 modulation of ion channels and inhibition of glial cell activation. 14 , 15 Recently, clinical trials have attempted to examine the feasibility and effectiveness of SAA for the treatment of knee OA in postmenopausal women 16 and older patients. 17 , 18 , 19 These studies were limited by a nonrandomized design, 19 no fidelity assessment, 16 and high attrition rate.…”
Section: Introductionmentioning
confidence: 99%
“…CAT is a method of treating illness that includes modalities such as herbal medicine, electroacupuncture (EA), acupuncture, cupping, yoga and meditation as a complementary or alternative to mainstream medicine. [ 10 ] CAT has been employed extensively recently to treat NP-related illnesses, including PHN, [ 11 ] fibromyalgia, [ 12 ] lumbar disc herniation, [ 13 ] peripherally induced NP, [ 14 ] etc. At the same time, although the number of studies is climbing year by year, there is a lack of quantitative analyses of research patterns, trends, and research hotspots regarding CAT for the treatment of NP.…”
Section: Introductionmentioning
confidence: 99%